Comparison of WC/C nanocomposite films in load-bearing capacity via interface micro-cracks during tribology behavior: A feasible judgment mechanism. Issue 17 (1st December 2019) - Ye, Yuwei; Chen, Hao; Guo, Shengda; Sun, Shangqi; Wang, Yongxin; Zhao, Haichao; Wang, Liping
Abstract: The WC/C nanocomposite films were deposited by unbalanced magnetron sputtering on the surface of 316 stainless steel, 2A14, H62 and Ti–6Al–4V substrates. The load-bearing capacity of WC/C film was characterized by indentation, scratch and friction tests. The failure mechanism of WC/C film was analyzed through the expansion of interface crack in different failure modes. Result showed that the stress relaxation at the interface was caused by crack, warp and deformation. Meanwhile, the substrate might fail earlier than the WC/C film under the effect of multi-strain. When the film and the substrate were in elastic deformation state, the load-bearing capacity of WC/C film was proportional to the mismatch strain energy of interface during sliding. In addition, the magnitude of mismatch strain energy under ideal condition could be quantified by the mismatch value. By comparison, the WC/C film deposited on 316 stainless steel displayed the highest load-bearing capacity during all specimens.